Prior agreement on revising the profit sharing ratio during the tenure of the contract in Musharakah and Mudarabah of Islamic banks - Sadique, Muhammad Abdurrahman (Zes Rokman Resources, 2018)
While it is generally ensured in equity based Islamic banking facilities that the profit sharing ratio is fixed at the inception of the contract, certain measures are seen to be adopted sometimes, that result in affecting the mechanism of profit sharing. These include reserving at the outset of the contract the option to alter the profit sharing ratio before the finalisation of the venture. The paper analyses a provision envisaging the possibility of adjusting the profit sharing ratio prior to liquidation of the partnership, with reference to accepted Islamic legal sources. It argues that such a provision does not seem appropriate in the prevalent environment of interest based banking, as it could become a means of defining the return of a partner, similar to interest based facilities. Introduction of such measures should be subject to careful assessment and revision by relevant bodies so as to avoid their harmful effects.